Early cognitive function, recovery and well-being after sevoflurane and xenon anaesthesia in the elderly: a double-blinded randomized controlled trial - Cremer, Jan (BioMed Central, 2011)
BACKGROUND: The postoperative cognitive function is impaired in elderly patients after general anaesthesia. The fast recovery after xenon anaesthesia was hypothesized to be advantageous in this scenario. We compared early postoperative cognitive function after xenon and sevoflurane anaesthesia in this study. METHODS: The study was approved by the local ethics committee and written informed consent was obtained from each patient. Patients aged 65-75 years (ASA I-III) scheduled for elective surgery (duration 60-180 min) were enrolled. Investigators performing cognitive testing and patients were blinded towards allocation to either xenon or sevoflurane anaesthesia. Baseline assessment of cognitive function was carried out 12-24 h before the operation. The results were compared to follow-up tests 6-12 and 66-72 h after surgery. Primary outcome parameter was the subtest "Alertness" of the computerized Test of Attentional Performance (TAP). Secondary outcome parameters included further subtests of the TAP, several Paper-Pencil-Tests, emergence times from anaesthesia, modified Aldrete scores and patients' well-being. RESULTS: 40 patients were randomized and equally allocated to both groups. No significant differences were found in the TAP or the Paper-Pencil-Tests at 6-12 and 66-72 h after the operation. All emergence times were faster after xenon anaesthesia. The modified Aldrete scores were significantly higher during the first hour in the xenon group. No difference in well-being could be detected between both groups. CONCLUSIONS: The results show no difference in the incidence of postoperative cognitive dysfunction (POCD) after xenon or sevoflurane anaesthesia. Emergence from general anaesthesia was faster in the xenon group.